TRANSPARANSI DALAM PELAYANAN PEMBUATAN E-KTP DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LOMBOK UTARA - Haerul Walad; Inka Nusamuda Pratama; Lalu Sopan Tirta Kusuma; Ilham Zitri (Nusantara Hasana Journal, 2024)
The Population and Civil Registration Service of North Lombok Regency is a government institution that provides services to the community, especially in population services. In 2013, the services provided by the Population and Civil Registration Service were still less than optimal and less transparent, especially in the service of making E-KTP. As a state institution tasked with providing maximum and transparent services, the Population and Civil Registration Service of North Lombok Regency must strive so that the community can get maximum and open services. The purpose of the study was to see the extent of transparency of services, especially in making E-KTP at the Population and Civil Registration Service of North Lombok Regency. This study uses a qualitative method to see the actual picture of what happened at the research location, with data collection techniques, namely interviews, observations, and documentation. Furthermore, the data obtained by the researcher was analyzed qualitatively. The results of this study illustrate that the service in making E-KTP by the Dukcapil Office of North Lombok Regency can be said to be transparent, because the Dukcapil party emphasizes three important aspects so that the service can be more optimal and transparent, namely: provision of clear information, ease of access to information, and the existence of publications related to the service flow, in this case the Dukcapil of North Lombok Regency utilizes social media such as Instagram and Facebook to publish related to the service flow provided. Driving factors and inhibiting factors for transparency of service in making E-KTP The driving factors for transparent service itself can be through strong leadership, committed leaders and competent human resources. The factors that have always been inhibiting transparent service are the first: Lack of commitment from leaders because the lack of commitment from leaders will inhibit transparent services, open and accountable practices.